Effects of silica fume and blast furnace slag on the mechanical properties and chloride ion distribution of coral aggregate concrete. (30th July 2019) - Wang, Yan; Zhang, Shaohui; Niu, Ditao; Su, Li; Luo, Daming
Highlights: Aggregates are fully replaced with coral fine aggregates and coral coarse aggregates. Mechanical properties CAC incorporation of SF and GBFS are studied. Effects of SF and GBFS on Cl - distribution brought by coral aggregate are studied. The theoretical total pore volume of CAC is evaluation from TG data. Abstract: Chloride attack is the severe problem that coral aggregate concrete (CAC) structure must face to in the application. Chloride ion distribution brings by coral aggregates is hence an important concern. This laboratory study explored the effects of silica fume (SF) and granulated blast furnace slag (GBFS) on the mechanical properties and chloride ion distribution brought by coral aggregates in CAC. Three types of CAC were designed including fly ash (FA), SF, and GBFS CAC, FA CAC was used as a reference sample. Apart from the compressive strength of CAC, the splitting tensile strength, total chloride content ( Ct ), free chloride content ( Cf ), and chloride binding capacity ( R ) were measured. The hydration products, theoretical total pore volume ( P ), and interfacial transition zone ( ITZ ) of CAC were characterized by X-ray powder diffraction, Thermogravimetric analysis, and Scanning Electron Microscopy. The result indicated that SF and GBFS had a negative effect on the compressive strength, splitting tensile strength and R of CAC at the early ages. The long-term Cf of CAC decreased by the addition of SF, while, this value rises with the GBFS content. The long-term R of CAC became stronger with SF content, but it became weaker with GBFS content. In addition, the large content of SF or GBFS decreased the P of CAC. The ITZ s of CAC became denser and homogeneous due to the pozzolanic activity of SF and GBFS as well as "internal curing" of coral aggregate.